Protocol for transcriptome-wide mapping of small-molecule RNA-binding sites in live cells - Yuquan Tong; Patrick R.A. Zanon; Xueyi Yang; Xiaoxuan Su; Jessica L. Childs-Disney; Matthew D. Disney (STAR Protocols, 2024)
Summary: Small molecules targeting RNA can be valuable chemical probes and potential therapeutics. The interactions between small molecules, particularly fragments, and RNA, however, can be difficult to detect due to their modest affinities and short residence times. Here, we present a protocol for mapping the molecular fingerprints of small molecules in vitro and throughout the human transcriptome in live cells. We describe steps for compound treatment, cross-linking, RNA extraction, fragmentation, and pull-down. We then detail procedures for RNA sequencing and data analysis.For complete details on the use and execution of this protocol, please refer to Tong et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.